2015
DOI: 10.1002/adsc.201500378
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Total Synthesis of (+)‐Gephyrotoxin 287C

Abstract: Gephyrotoxin 287C, a bioactive alkaloid bearing a perhydropyrrolo[1,2‐a]quinoline skeleton with five stereocenters, is an attractive target for synthetic organic chemistry. We achieved an enantioselective total synthesis of (+)‐gephyrotoxin 287C, for which the key steps were palladium‐catalyzed asymmetric allylic amination using a chiral diaminophosphine oxide (DIAPHOX) preligand, diastereoselective intramolecular Mannich reaction, and tin tetrachloride‐catalyzed diastereoselective conjugate addition/protonati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…279 These reactions have been applied to the formation of chiral centres in synthesis of biologically active products 285 and even to total syntheses. 284,286 It should be noted that Nemoto and Hamada 10,45,49 have reviewed the application of the DIAPHOX ligands to allylic substitution and the reader is directed to these reviews to have the full account of their applicability.…”
Section: -99% Yield 72-93% Eementioning
confidence: 99%
“…279 These reactions have been applied to the formation of chiral centres in synthesis of biologically active products 285 and even to total syntheses. 284,286 It should be noted that Nemoto and Hamada 10,45,49 have reviewed the application of the DIAPHOX ligands to allylic substitution and the reader is directed to these reviews to have the full account of their applicability.…”
Section: -99% Yield 72-93% Eementioning
confidence: 99%
“…Although the scarcity of these natural products and their neurological profile has stimulated considerable synthetic efforts in this area, only three enantioselective total syntheses of gephyrotoxin 287C have been reported to date. , The first one, using l -pyroglutamic acid as the source of chirality, generated a controversy about the absolute configuration of natural gephyrotoxin 287C, as the synthesized 1 S ,3a S ,5a S ,6 S ,9a R enantiomer appeared to be dextrorotatory, in contrast with the isolated natural product, which had been reported as levorotatory. , However, two recent independent enantioselective syntheses unambiguously confirmed that the absolute configuration of (−)-gephyrotoxin 287C is 1 S ,3a S ,5a S ,6 S ,9a R (X-ray analysis of the hydrochloride salt) and that (+)-gephyrotoxin 287C is the 1 R enantiomer…”
mentioning
confidence: 99%